(3OjhGf GdCYSes - (3YHGS GdCYSes ((3eMeO Hf GdTjN WGgQ GdSeGhj s)
(3ChdgG (B:s
(3agPG OjhGf GdaGVd GdTjN YHGS GdCYSe LeYJg ef ChQGb HNWg, hQJHJg Ydi GdMQha hCdMbJ HBNQg GdJNGejS s
(3BNQgG (B:s
(3hEffj YfOeG bO SQge Cdej bO SQfj Cfge bO SQge Sbej aGROOJ cjeG jSQhG aj Gdghi SbeG s
(3cJHJ YfGhjf HYV GdbUGFO HGdeOGO GdCMeQs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B28 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs